Atuação das lideranças do Movimento Negro Unificado no processo de aprovação da Lei 10.639/2003 e sua implicação na mudança dos livros didáticos de história - SILVA, Humberto Rafael de Andrade (2019)
The present work aims to investigate the contribution of the activists from the contemporary Unified Black Movement (“Movimento Unificado Negro”, also known as “MNU”) to the approval of Law 10.639/2003, which provides for the mandatory teaching of African and Afro-Brazilian History in Brazilian public school institutions, as well as how this law has affected History textbooks. The textbook was chosen because it is the most used artifact by students and teachers in Brazilian classrooms; whose narrative is massively diffused in childhood and teenage educational process, its content constantly undergoes the state’s scrutiny, and it seeks to be the curriculum’s mirror instituted by the State itself. A historiographical review is made in this work regarding since the first bills that provided for the teaching of African and Afro-Brazilian History within the post re-democratization context, until the approval of Law 10.639/2003 at the beginning of the 21st century. In this process, we sought to give visibility to the actors who joined the process of building up projects in the same area that preceded the law, as well as the final project itself. The main research sources used were the National Plenary websites to check the bills, besides the MNU activists’ biographies, academic articles, dissertations and theses. The action of the Unified Black Movement and its activists in the process of a law’s approval has a fundamentally educational competence and also a practical repercussion, once this act, from the law’s demand as well as other guidelines that intended to combat prejudice, is responsible for the continued elimination of prejudice in our society.